2011
DOI: 10.1016/j.ymgme.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy of enzyme replacement therapy in Pompe disease through mannose-6-phosphate receptor expression in skeletal muscle

Abstract: Enzyme replacement therapy (ERT) with acid α-glucosidase has become available for Pompe disease; however, the response of skeletal muscle, as opposed to the heart, has been attenuated. The poor response of skeletal muscle has been attributed to the low abundance of the cation-independent mannose-6-phosphate receptor (CI-MPR) in skeletal muscle compared to heart. To further understand the role of CI-MPR in Pompe disease, muscle-specific CI-MPR conditional knockout (KO) mice were crossed with GAA-KO (Pompe disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 30 publications
9
89
1
Order By: Relevance
“…[11][12][13] The underlying mechanism of the therapeutic action of clenbuterol might be related to insulin-like growth factor (IGF)-1-mediated muscle hypertrophy, which has been correlated with increased CI-MPR (also known as IGF-2 receptor) expression. 14 In the present study, we evaluated a combination of anti-CD4 mAb and clenbuterol to induce immune tolerance and to increase CI-MPR-mediated uptake and trafficking of GAA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The underlying mechanism of the therapeutic action of clenbuterol might be related to insulin-like growth factor (IGF)-1-mediated muscle hypertrophy, which has been correlated with increased CI-MPR (also known as IGF-2 receptor) expression. 14 In the present study, we evaluated a combination of anti-CD4 mAb and clenbuterol to induce immune tolerance and to increase CI-MPR-mediated uptake and trafficking of GAA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…enhance rhGAA uptake in heart or skeletal muscle. Recombinant enzyme uptake following intravenous injection may be primarily regulated at the level of the cation-independent mannose-6-phosphate receptor (CI-MPR) [8,21], and tissue perfusion characteristics may be of secondary importance. Alternatively, chaperone therapy with imino sugars [54] or venous infusion of L-arginine and N-acetylcysteine [55,56] may improve nitric oxide bioavailability and rhGAA delivery with potential antioxidant benefits.…”
Section: Resultsmentioning
confidence: 99%
“…muscle is more treatment resistant vs. cardiac tissue) [4,6]. Furthermore, fast-twitch fibers (glycolytic, IIx/IIb; oxidative/glycolytic, IIa) appear more refractory to ERT than slow-twitch fibers (oxidative, I) [7], possibly due to a lower abundance of cation-independent mannose-6-phosphate receptors (CI-MPR) [6,8,9], an impaired ability to undergo autophagic flux [10], and/or differential perfusion characteristics between fibers [11]. Autophagic buildup in fast fibers has been shown to prevent efficient trafficking of exogenous rhGAA to the lysosomes in Pompe mice [12], thereby reducing the bioavailability of the drug and lysosomal glycogen clearance compared to slow fibers [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations may in part explain the contribution of ERT to a shift of disease burden from mortality to morbidity; infants who would have died of progressive cardiac involvement are now living longer only to manifest a more protracted course of muscle weakness and risk of respiratory complications, i.e., unless started on ERT before development of clinically noticeable motor weakness. The attenuated skeletal muscle response to ERT has been attributed to many factors such as the degree of pre-ERT muscle damage, humoral immunity, and paucity of mannose 6 phosphate receptors (M-6-P), the latter was the focus of Koeberl et al's recent publication in which they demonstrated the positive role of increasing M-6-P expression in mice, using the b2-agonist therapy with clenbuterol, on enhancing the efficacy of ERT in Pompe disease (Koeberl et al 2011). Until such strategies are clinically proven, the best chance for these patients remains in initiating ERT before onset of weakness.…”
Section: Discussionmentioning
confidence: 99%